The Performance Mapping and Measurement Handbook. - Harbour, Jerry L. (CRC Press, 2013)
To better understand and improve your systems, you must measure and map their essential characteristics. Yet, because your systems and their associated processes occur over varying spatial and temporal scales, you will need various types of maps and metrics-depending on the level of detail and understanding required. During nearly four decades of experience helping clients across various industries understand, measure, and improve the performance of their processes, Jerry L. Harbour discovered a handful of performance maps that will work in most settings. As such, he's gathered these critical.